Correlation of microalbumin and sialic acid with anthropometric variables in type 2 diabetic patients with and without nephropathy - B Shivananda Nayak; Heidi Duncan; Sunita Lalloo; Kevin Maraj; Vani Matmungal; et al (Vascular Health and Risk Management, 2008)
B Shivananda Nayak, Heidi Duncan, Sunita Lalloo, Kevin Maraj, Vani Matmungal, Felicia Matthews, Bhupinder Prajapati, Ria Samuel, Pearse SylvesterDepartment of Preclinical Sciences, Biochemistry Unit, The University of the West Indies, Trinidad, West IndiesAim: The objective of this study is to correlate microalbumin and sialic acid levels with anthropometric variables in type 2 diabetic patients with and without nephropathy.Methods: This study was a case control study and included 108 Trinidadian subjects (aged 15–60 years) of which 30 were healthy individuals, 38 had type 2 diabetes, and 40 were of type 2 diabetic patients with nephropathy. Blood pressure and waist to hip ratio were recorded. Fasting venous blood samples and urine samples were collected from all the subjects. Blood samples were analysed for the glucose, C-reactive protein, and sialic acid. Urine sample was analysed for microalbumin and sialic acid.Results: Urinary microalbumin was higher among diabetic subjects (28.9 ± 30.3 mg/L) compared with controls (8.4 ± 10.2 mg/L) and was significantly higher in diabetic patients with nephropathy (792.3 ± 803.9 mg/L). Serum sialic acid was higher in subjects with diabetic nephropathy (71.5 ± 23.3 mg/dL) compared to diabetics (66.0 ± 11.7 mg/dL) and controls (55.2 ± 8.3 mg/dL). Increased microalbumin and sialic acid were correlated with other cardiovascular risk factors such as hypertension and waist to hip ratios (p < 0.05).Conclusions: From these results it can be concluded that the increased microalbumin and sialic acid were strongly correlated with hypertension and waist to hip ratios in Trinidadian type-2 diabetic patients. Measurement of sialic acid, microalbumin, and waist to hip ratio along with the blood pressure is recommended for all type 2 diabetic patients to reduce the cardiovascular risk.Keywords: sialic acid; microalbumin; diabetes